Currículo innovador para niños considerados académicamente limítrofes (2000)
This is a curricular proposal for Mild Mentally Retarded Chindren agen seven to eighteen.The program intends to give answer to children’s academic, psycological and social needs as well as to help them to reach personal independence. The curriculum theoretical support comes from the Sociocultural Developmental Theo¬ries; mainly Vigotsky’s position related to the Zone of Proximal Development. The proposal includes the description of all the curriculum aspects, the possibility to carry it out and to make the adjustments for its practical improvement.